(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study is to find out whether visual and auditory reaction time (VRT and ART) is influenced by Ramadan fasting in healthy individuals in terms of neuro performance. Materials and Methods: 60 healthy individuals (30 male, 30 female) with the mean age of 20.22±1.45 years participated in the study. First reaction measurement was collected on the second week of the date Ramadan fasting started and this period was called fasting period. Second reaction measurement was collected five days after Ramadan fasting ended and this period was called post-fasting period. VRT and ART of the samples who participated in the study were made with reaction timer device. 10 trials for sound and light stimuli were taken from each sample. The first five trials were considered as exercise and the average of the last five trials was determined as reaction time. The analysis of VRT and ART in fasting and post-fasting periods was conducted with Wilcoxon matched pairs test. In addition, Mann Whitney U test was used to analyze whether there were differences between fasting and post-fasting periods of males and females in terms of VRT and ART. Results: No statistical difference was found between the VRT and ART of males and females in fasting and post-fasting period (p>0.05). Conclusion: In this study which examined the effect of fasting on VRT and ART, it was found that males and females who participated in this study were not negatively influenced by Ramadan fasting in terms of neuro performance.